INTEGRASI BAHASA INGGRIS DAN MATA PELAJARAN KEJURUAN TEKNIK KOMPUTER DAN JARINGAN MELALUI KOLABORASI GURU DI SMK - Widiayanti, Rina; Maghfiroh, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The integration of English with vocational subjects has become an essential strategy for improving students' readiness to meet the demands of the global workforce. This study aims to analyze the implementation of English integration into the Computer and Network Engineering (TKJ) vocational subject through teacher collaboration at SMKN 1 Sawoo. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, vice principal for curriculum, English teachers, TKJ teachers, and students. The findings reveal that the integration is implemented through the alignment of learning materials, the use of technical English vocabulary, authentic learning resources, and collaborative planning between English and vocational teachers. Teacher collaboration contributes positively to students' understanding of technical terminology, reading comprehension of technical documentation, and confidence in using English during practical activities. However, challenges remain, including students' varying English proficiency, limited coordination time among teachers, and the absence of integrated teaching modules. The study concludes that collaborative integration of English and vocational learning enhances contextual learning experiences and supports the development of vocational competencies required in the digital era.